Maximal and minimal iterative positive solutions for singular infinite-point p-Laplacian fractional differential equations - Guo, Limin; Liu, Lishan (Nonlinear Analysis: Modelling and Control, 2019)
The existence of maximal and minimal positive solutions for singular infinite-point p-Laplacian fractional differential equation is investigated in this paper. Green’s function is derived, and some properties of Green’s function are obtained. Based upon these properties of Green’s function, the existence of maximal and minimal positive solutions is obtained, and iterative schemes are established for approximating the maximal and minimal positive solutions.